Needs analysis for electronic teaching materials based on the merdeka learning pathway to enhance students' mathematical creative thinking skills - Jumrah, Jumrah; Sukmawati, Sukmawati; Nasrun, Nasrun (Universitas Islam Negeri (UIN) Mataram, 2025)
[English]: This research aims to analyze the needs and characteristics of electronic teaching materials based on the Merdeka Learning Pathway that are relevant to student conditions and capable of addressing challenges in mathematics learning. The study focuses on the analysis stage within the ADDIE development model. Data collection techniques included interviews and questionnaires, structured based on curriculum analysis, student characteristics analysis, and learning objectives analysis within the ADDIE development model. Data were analyzed using descriptive qualitative and quantitative methods to identify the needs and characteristics of the teaching materials. Findings indicate a significant gap in students' mathematical creative thinking skills. Although teachers acknowledge the role of technology, existing electronic teaching materials are insufficient in promoting creativity and independent learning. Students also expressed a need for electronic learning resources that are flexible, interactive, and contextual. Specifically, most students experienced difficulties in independent learning without systematically structured teaching materials. Therefore, the development of adaptive electronic teaching materials, integrated with interactive elements (e.g., animations, simulations), contextual problems, and exploratory activities based on the Merdeka Learning Pathway, is highly recommended to bridge this gap, support differentiated learning, and enhance students' mathematical creative thinking skills. [Bahasa]: Penelitian ini bertujuan untuk menganalisis kebutuhan dan karakteristik bahan ajar elektronik berbasis alur merdeka yang relevan dengan kondisi siswa dan mampu menjawab tantangan pembelajaran matematika. Penelitian ini berfokus pada tahap analysis dalam model pengembangan ADDIE. Teknik pengumpulan data meliputi wawancara dan angket yang disusun berdasarkan hasil analisis kurikulum, analisis karakteristik siswa dan analisis tujuan pembelajaran dalam model pengembangan ADDIE. Data dianalisis secara deskriptif kualitatif dan kuantitatif untuk mengidentifikasi kebutuhan serta karakteristik bahan ajar. Temuan menunjukkan adanya kesenjangan signifikan dalam keterampilan berpikir kreatif matematis siswa. Meskipun guru mengakui peran teknologi, bahan ajar elektronik yang ada belum cukup dalam mendorong kreativitas dan kemandirian belajar. Siswa juga menyatakan kebutuhan akan sumber belajar elektronik yang fleksibel, interaktif, dan kontekstual. Secara khusus, mayoritas siswa mengalami kesulitan belajar mandiri tanpa bahan ajar yang terstruktur secara sistematis. Oleh karena itu, pengembangan bahan ajar elektronik adaptif, yang terintegrasi dengan elemen interaktif (misalnya, animasi, simulasi), masalah kontekstual, dan aktivitas eksploratif berbasis Alur Merdeka, sangat direkomendasikan untuk menjembatani kesenjangan tersebut dan mendukung pembelajaran berdiferensiasi, serta meningkatkan keterampilan berpikir kreatif matematis siswa.